2011
DOI: 10.1016/j.neuropsychologia.2011.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Early error detection is generic, but subsequent adaption to errors is not: Evidence from ERPs

Abstract: The aim of the present study was to investigate whether error detection and subsequent regulatory processes could be influenced by pre-familiarisation with task-relevant stimulus features. To this end, nineteen healthy adults performed a speeded Go/NoGo task with compound targets, involving two concurrent stimulus attributes, which were either prefamiliarised or not, while high-density EEG was recorded. During the speeded Go/NoGo task, response errors clearly elicited an error-related negativity (ERN) and erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 69 publications
(83 reference statements)
3
21
1
Order By: Relevance
“…In this study, using EMG-locked ERPs, the generator of the ERN was found to be localised in the posterior cingulate (PCMA, area 23), consistent with previous ERP studies using a similar Go/Nogo task [37][40]. Yet ,this early monitoring effect was located more posteriorly compared to previous anatomical or brain-imaging studies, that have typically evidenced early error-related effects (or post-error effects) situated in more anterior medial-frontal regions, including in the posterior medial frontal cortex [58].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, using EMG-locked ERPs, the generator of the ERN was found to be localised in the posterior cingulate (PCMA, area 23), consistent with previous ERP studies using a similar Go/Nogo task [37][40]. Yet ,this early monitoring effect was located more posteriorly compared to previous anatomical or brain-imaging studies, that have typically evidenced early error-related effects (or post-error effects) situated in more anterior medial-frontal regions, including in the posterior medial frontal cortex [58].…”
Section: Discussionsupporting
confidence: 90%
“…A standard speeded Go/Nogo task [37][40] was used in order to collect false alarms, which could be consciously detected (i.e. aware errors) or not (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with previous ERP studies using this Go/noGo task (Aarts & Pourtois, 2010;Dhar & Pourtois, 2011), and given the speed pressure imposed on participants as well as the relatively high number of errors committed within a short period of time, the ERN/Ne-CRN amplitude difference was actually modest at this specific electrode position (FCz), though being significant, suggesting that response errors were discriminated from hits early on following response onset, especially so for MDD patients.…”
Section: Erp Componentssupporting
confidence: 86%
“…Interestingly, a number of EEG source localization studies have suggested that motor regions such as the cingulate motor area and the presupplementary motor area (pre-SMA) are the generator sites of the ERN as opposed to the ACC (Dhar and Pourtois 2011; Hochman et al 2009; Badgaiyan and Posner 1998; Dehaene et al 1994; Miltner et al 1997). These motor regions not only take part in higher order motor executive control and self-initiated movements, but also contribute to sequential movements and adaptive motor learning (Chao et al 2009; Duann et al2009; Stuphorn et al 2010; Chen et al 2010; Nachev et al 2005; Cunnington et al2002; Shima et al 1996; Chen and Wise 1996; Hikosaka et al 1996).…”
Section: Feedback Error Processing In the Accmentioning
confidence: 99%
“…Whether the error processing mechanisms of the cingulate motor area and the pre-SMA are distinct from those of the medial prefrontal/ACC regions during cognitive control tasks is debatable. Considering the relative anatomical closeness of these regions and the evidence suggesting that the cingulate motor area and the pre-SMA may also be generator sites of the ERN signal (Nachev et al 2008; Dhar and Pourtois 2011; Hochman et al 2009; Badgaiyan and Posner 1998; Dehaene et al1994; Miltner et al 1997), one might argue that these regions serve similar functions. However, it has been proposed that the cingulate motor area and the pre-SMA correct for movement errors in a proactive manner (Isoda and Hikosaka 2007).…”
Section: Feedforward Error Processing In the Accmentioning
confidence: 99%